TRPA1-dependent and -independent activation by commonly used preservatives - Mager, Maximilian L.; Ciotu, Cosmin I.; Gold-Binder, Markus; Heber, Stefan; Fischer, Michael J. M. (Frontiers in Pharmacology, 2023)
Addition of preservatives ensures microbial stability, especially in multidose containers of parenterally administered pharmaceuticals. These compounds can cause side effects, and particularly at the site of application, might elicit or facilitate pain. TRPA1 is a cation channel expressed in peripheral neurons which contributes to pain and inflammation and is sensitive to many irritants. The most commonly used preservatives, in particular with a focus on parenteral formulations, were investigated for their potential to activate TRPA1.Sixteen preservatives were screened for mediating calcium influx in human TRPA1-transfected HEK293t cells. Untransfected cells served as control, results were further validated in mouse sensory neurons. In addition, proinflammatory mediators serotonin, histamine and prostaglandin E2 were coadministered to probe a potential sensitisation of preservative-induced TRPA1 activation.Butylparaben, propylparaben, ethylparaben, bronopol, methylparaben, phenylethyl alcohol and phenol induced a TRPA1-dependent calcium influx in transfected HEK293t cells at concentrations used for preservation. Other preservatives increased calcium within the used concentration ranges, but to a similar degree in untransfected controls. Serotonin, histamine, and prostaglandin enhanced TRPA1 activation of phenylethyl alcohol, bronopol, ethylparaben, propylparaben and butylparaben.Systematic screening of common preservatives applied for parenterally administered drugs resulted in identifying several preservatives with substantial TRPA1 channel activation. This activation was enhanced by the addition of proinflammatory meditators. This allows selecting a preservative without TRPA1 activation, particularly in case of pharmaceuticals that could act proinflammatory.